Efficient light conversion adhesive film and preparation method thereof
By grafting functional functional groups on the light-transforming material, the optical performance is optimized, and the light loss problem caused by self-absorption of the existing light-transforming material is solved, thus achieving efficient conversion of unused UV ultraviolet light into visible light, improving photovoltaic Component performance and stability.
Patent Information
- Application Number
- CN202411734303.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-11
AI Technical Summary
The existing light-transforming materials have a wide optical self-absorbing property, which leads to light loss problems, and the emitted blue light has limited gain in practical applications of TOPCon and HJT batteries.
Provides an efficient optical conversion adhesive film, which optimizes its absorption and emission spectrum by grafting functional groups on the optical conversion material, improves its compatibility and dispersion, thereby reducing optical loss and maximizing the use of unused UV ultraviolet light converts it into visible light.
It effectively solves the light loss problem caused by self-absorption, improves the light utilization rate and power generation power of photovoltaic modules, and improves the stability and service life of the modules.
Smart Images

Figure CN119410294A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic adhesive films, and in particular to a high-efficiency light-conversion adhesive film and a preparation method thereof. Background Art
[0002] The band gap of crystalline silicon solar cell modules determines that they can absorb sunlight with energy higher than the band gap energy before 1100nm, and the response of crystalline silicon solar cells to ultraviolet light in the band below 380nm is very weak, while photovoltaic modules are relatively sensitive to ultraviolet light. Long-term exposure of modules to ultraviolet light will greatly reduce the life of the modules and other practical problems.
[0003] At present, existing photovoltaic modules mostly use light conversion materials added to the module packaging film to convert the low-utilization ultraviolet light in sunlight into usable visible light, thereby achieving the purpose of improving light utilization, increasing module power and increasing module service life. However, the existing light conversion materials have a wide optical self-absorption, so that the emitted light of the light conversion material will be absorbed by the material itself, resulting in light loss problems, and the emitted blue light has limited gain in the actual application of TOPCon and HJT cells. Summary of the invention
[0004] The purpose of the present invention is to address the problem of light loss caused by the existing light conversion materials due to their own wide optical self-absorption. The present invention provides a new high-efficiency light conversion adhesive film, which effectively solves the problem of light loss caused by self-absorption, maximizes the use of unused UV ultraviolet light, and converts it into visible light that can be highly absorbed by batteries, thereby improving the light utilization rate of optical components and increasing the power generation capacity of the components.
[0005] To achieve the above object, the present invention is implemented by the following technical solutions:
[0006] The present invention provides a high-efficiency light-converting adhesive film, which comprises the following components in parts by weight:
[0007] 100 parts of base resin, 0.01-5.0 parts of cross-linking agent, 0.01-4.0 parts of auxiliary cross-linking agent, 0.01-5.0 parts of coupling agent and 0.2-10.0 parts of grafted light conversion material;
[0008] Wherein: the grafted light conversion material is a material obtained by grafting vinyl, methoxy or amino functional groups at the end of the light conversion material, and the Stokes shift of the grafted light conversion material is ≥150nm, the emission band is 600-650nm, the emission peak is 610-630nm, and the light conversion efficiency of the grafted light conversion material is ≥85%.
[0009] Specifically, the basic resin in the present invention may be POE or EVA particles.
[0010] Furthermore, a high-efficiency light-converting adhesive film is provided: the light-converting adhesive film comprises the following components in parts by weight: 100 parts of base resin, 0.05 parts of cross-linking agent, 1.0 parts of auxiliary cross-linking agent, 3.0 parts of coupling agent and 5.0 parts of grafted light-converting material.
[0011] Furthermore, a highly efficient light-converting adhesive film: the particle size of the grafted light-converting material is 5.0 to 20.0 nm.
[0012] Furthermore, a highly efficient light-converting adhesive film: the crosslinking agent is a peroxide crosslinking agent selected from any one of diisopropylbenzene peroxide, di(tert-butylperoxyisopropyl)benzene or 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.
[0013] Furthermore, a high-efficiency light-converting adhesive film: the auxiliary cross-linking agent is selected from at least one of trimethylol trimethacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, N,N′-p-phenyl bismaleimide, zinc diacrylate, and zinc dimethacrylate.
[0014] The present invention also provides a method for preparing a high-efficiency light-converting adhesive film, which comprises the following specific steps:
[0015] S1. Preparation of grafted light conversion material: mixing the light conversion material or light conversion material precursor, the functional monomer containing vinyl, methoxy or amino functional groups, and the crosslinking initiator in a stirrer, and bonding the crosslinking initiator and the functional monomer to the light conversion material by microwave or infrared energy projection, thereby forming the grafted light conversion material;
[0016] S2. Preparation of high-efficiency light-converting adhesive film: accurately weigh the base resin, cross-linking agent, auxiliary cross-linking agent, coupling agent and grafted light-converting material by weight, mix them thoroughly and add them into the extruder, cast them into a film through a die head, and heat treat them to obtain a high-efficiency light-converting adhesive film.
[0017] The preparation of the grafted light conversion material can be carried out in two steps: first synthesizing the light conversion material and then grafting the functional groups. Alternatively, the functional groups can be grafted while synthesizing the light conversion material (via a light conversion material precursor).
[0018] Beneficial effects of the present invention:
[0019] (1) In order to solve the problem of light loss caused by wide optical self-absorption in existing light conversion materials, the present invention provides a high-efficiency light conversion adhesive film, which selects a light conversion material of a suitable wavelength and grafts functional groups thereon, so that the compatibility and dispersibility of the light conversion material in the adhesive film are good, the absorption and emission spectra of the light conversion material are optimized, and the light loss problem caused by self-absorption is effectively solved. The unused UV light is utilized to the greatest extent and converted into visible light that can be highly absorbed by the battery, thereby improving the light utilization rate of the photovoltaic module and increasing the power generation capacity of the module.
[0020] (2) The high-efficiency light-converting adhesive film of the present invention also solves the problem of uneven dispersion of the light-converting material in the adhesive film and the existence of concentration differences. The present invention introduces functional groups such as methoxy, vinyl silane, and amino groups on the surface of the light-converting material and grafts them onto the molecular chain of the matrix resin of the light-converting adhesive film through reaction, so that the mobility of the light-converting material at high temperature is greatly reduced, thereby effectively improving the stability of the light-converting adhesive film of the present invention.
[0021] (3) The grafted light conversion material of the present invention can enhance the solubility of the light conversion material in the film and inhibit the migration and aggregation of the light conversion material in the film. After cross-linking, the functional groups are introduced into the molecular chain of the matrix resin through monomer-involved copolymerization or free radical-induced grafting reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 This is a microscopic morphology of the light-converting adhesive film obtained in Comparative Example 1;
[0024] Figure 2 This is a microscopic morphology of the light-converting adhesive film obtained in Example 1. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] This embodiment 1 provides a high-efficiency light-converting adhesive film, which includes the following components in parts by weight:
[0028] 100 parts of EVA matrix resin, 0.05 parts of peroxide crosslinking agent (dicumyl peroxide), 1.0 parts of auxiliary crosslinking agent (trimethylol trimethacrylate), 3.0 parts of silane coupling agent and 5.0 parts of grafted light conversion material;
[0029] Wherein: the grafted light conversion material is a material obtained by grafting a vinyl functional group at the end of the light conversion material, and the Stokes shift of the grafted light conversion material is 150nm, the emission band is 600-650nm, the emission peak is 610nm, and the light conversion efficiency of the grafted light conversion material is ≥85%.
[0030] The method for preparing the high-efficiency light-converting adhesive film of the above-mentioned embodiment 1 comprises the following specific steps:
[0031] S1. Preparation of grafted light conversion material: mixing the light conversion material, the functional monomer containing vinyl functional groups (a mixture of KH570 and TAIC), and the crosslinking initiator in a stirrer, and bonding the crosslinking initiator (TBEC) and the functional monomer to the light conversion material by infrared energy projection, thereby forming the grafted light conversion material;
[0032] S2. Preparation of high-efficiency light-converting adhesive film: accurately weigh 100 parts of EVA matrix resin, 0.05 parts of peroxide cross-linking agent, 1.0 parts of auxiliary cross-linking agent, 3.0 parts of silane coupling agent and 5.0 parts of grafted light-converting material by weight, mix them thoroughly and add them to the extruder, cast them into a film through a die head, and heat treat them to obtain a high-efficiency light-converting adhesive film.
[0033] Example 2
[0034] This embodiment 2 provides a high-efficiency light-converting adhesive film, which includes the following components in parts by weight:
[0035] 100 parts of POE matrix resin, 2.0 parts of peroxide crosslinking agent (di(tert-butylperoxyisopropyl)benzene), 0.03 parts of auxiliary crosslinking agent (ethylene glycol dimethacrylate), 0.5 parts of silane coupling agent and 8.0 parts of grafted light conversion material;
[0036] Wherein: the grafted light conversion material is a material obtained by grafting a vinyl functional group at the end of the light conversion material, and the Stokes shift of the grafted light conversion material is ≥150nm, the emission band is 600-650nm, the emission peak is 610-630nm, and the light conversion efficiency of the grafted light conversion material is ≥85%.
[0037] The method for preparing the high-efficiency light-converting adhesive film of the above-mentioned embodiment 2 comprises the following specific steps:
[0038] S1. Preparation of grafted light conversion material: mixing the light conversion material, the functional monomer containing a methoxy functional group (VTMS), and the cross-linking initiator in a stirrer, and bonding the cross-linking initiator (TAEC) and the functional monomer to the light conversion material by microwave energy projection, thereby forming the grafted light conversion material;
[0039] S2. Preparation of high-efficiency light-converting adhesive film: Accurately weigh 100 parts of POE matrix resin, 2.0 parts of peroxide cross-linking agent, 0.03 parts of auxiliary cross-linking agent, 0.5 parts of silane coupling agent and 8.0 parts of grafted light-converting material by weight, mix them thoroughly and add them to the extruder, cast them into a film through a die head, and heat treat them to obtain a high-efficiency light-converting adhesive film.
[0040] Example 3
[0041] This embodiment 3 provides a high-efficiency light-converting adhesive film, which includes the following components in parts by weight:
[0042] 100 parts of EVA matrix resin, 5.0 parts of peroxide crosslinking agent (selected as 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane), 3.0 parts of auxiliary crosslinking agent (selected as N,N′-p-phenylbismaleimide), 1.5 parts of silane coupling agent and 5.0 parts of grafted light conversion material;
[0043] Wherein: the grafted light conversion material is a material obtained by grafting a vinyl functional group at the end of the light conversion material, and the Stokes shift of the grafted light conversion material is ≥150nm, the emission band is 600-650nm, the emission peak is 610-630nm, and the light conversion efficiency of the grafted light conversion material is ≥85%.
[0044] The method for preparing the high-efficiency light-converting adhesive film of the above-mentioned embodiment 3 comprises the following specific steps:
[0045] S1. Preparation of grafted light conversion material: mixing the light conversion material, the functional monomer containing an amino functional group, and the crosslinking initiator in a stirrer, and bonding the crosslinking initiator and the functional monomer to the light conversion material by microwave energy projection, thereby forming the grafted light conversion material;
[0046] S2. Preparation of high-efficiency light-converting adhesive film: accurately weigh 100 parts of EVA matrix resin, 5.0 parts of peroxide cross-linking agent, 3.0 parts of auxiliary cross-linking agent, 1.5 parts of silane coupling agent and 5.0 parts of grafted light-converting material by weight, mix them thoroughly and add them to the extruder, cast them into a film through a die head, and heat treat them to obtain a high-efficiency light-converting adhesive film.
[0047] Comparative Example 1
[0048] Comparative Example 1 provides a light-converting adhesive film, which includes the following components in parts by weight: 100 parts of base resin, 0.05 parts of peroxide cross-linking agent, 1.0 parts of auxiliary cross-linking agent, 3.0 parts of silane coupling agent and 5.0 parts of light-converting material.
[0049] The difference between Comparative Example 1 and Example 1 is that: Comparative Example 1 directly uses the same light conversion material as Example 1 to obtain a light conversion adhesive film, but Comparative Example 1 does not graft functional groups to the light conversion material, and the rest is the same as Example 1.
[0050] Comparative Example 2
[0051] Comparative Example 2 provides a light-converting adhesive film, which includes the following components in parts by weight: 100 parts of base resin, 0.05 parts of peroxide cross-linking agent, 1.0 parts of auxiliary cross-linking agent, 3.0 parts of silane coupling agent and 5.0 parts of light-converting material A;
[0052] Among them, the light conversion material A is a light conversion material on the market, but its Stokes shift is small and there is self-absorption. Its emission band is 400-450nm and the emission peak is 415nm. The light conversion efficiency of the light conversion functional monomer is ≥90%.
[0053] Comparative Example 3
[0054] Provided is an adhesive film, which comprises the following components in parts by weight: 100 parts of a base resin, 0.05 parts of a peroxide cross-linking agent, 1.0 parts of an auxiliary cross-linking agent, and 3.0 parts of a silane coupling agent.
[0055] The difference between Comparative Example 3 and Example 1 is that the adhesive film of Comparative Example 3 is not doped with light conversion material.
[0056] test:
[0057] The light conversion gain and mobility comparison test was performed on the light conversion adhesive films of the above-mentioned embodiment 1, comparative example 1 and comparative example 2. The test process is: the light conversion adhesive films of embodiment 1, comparative example 1 and comparative example 2 were applied to the HJT components for testing. The results are shown in the following table:
[0058]
[0059] It can be seen from the test results in the above table that the high-efficiency light-conversion adhesive film provided in Example 1 of the present invention can increase the component power by about 0.8% compared with the adhesive film of the same formula without adding light-conversion material (Comparative Example 3), and the mobility under ultraviolet aging and high temperature is also greatly reduced, thereby improving the stability and service life of the component.
[0060] It can also be seen from the test results of Example 1 and Comparative Example 1 that the present invention enhances the solubility of the light conversion material in the film by grafting functional groups on the light conversion material, inhibits the migration and agglomeration of the light conversion material in the film, and significantly reduces the mobility. At the same time, compared with the light conversion material of Comparative Example 1, it also effectively improves the component power.
[0061] like Figure 1 As shown, the light-conversion material of Comparative Example 1 is not grafted with functional groups. After the light-conversion adhesive film is made, the light-conversion material is free in the film matrix resin. This makes the mobility of the light-conversion adhesive film of Comparative Example 1 very high under ultraviolet aging and high temperature, resulting in poor stability of the light-conversion adhesive film. Figure 2 As shown, in the light-converting adhesive film of Example 1 of the present invention, the light-converting material is linked to the adhesive film matrix resin, so that the mobility of the light-converting adhesive film under ultraviolet aging and high temperature is greatly reduced.
[0062] In the cross-linking process of Example 1, the functional monomer molecules will participate in the cross-linking and curing of the EVA encapsulation film. The functional groups in the monomers react with the long chains of EVA. The functional monomers are used as "bridges" to connect the functional groups of the functional monomers to the side chains of the EVA ester groups, thereby extending the EVA chains. The ester groups suspended on the long chains of the EVA are firmly anchored in the body structure trap after cross-linking, which significantly reduces the mobility of the light-converting material in the film.
[0063] The above are preferred embodiments of the present invention and are only used to explain the present invention, not to limit the present invention. Any obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A highly efficient light-converting adhesive film, characterized in that: The light-converting adhesive film comprises the following components in parts by weight: 100 parts of base resin, 0.01-5.0 parts of cross-linking agent, 0.01-4.0 parts of auxiliary cross-linking agent, 0.01-5.0 parts of coupling agent and 0.2-10.0 parts of grafted light conversion material; Wherein: the grafted light conversion material is a material obtained by grafting vinyl, methoxy or amino functional groups at the end of the light conversion material, and the Stokes shift of the grafted light conversion material is ≥150nm, the emission band is 600-650nm, the emission peak is 610-630nm, and the light conversion efficiency of the grafted light conversion material is ≥85%.
2. The high-efficiency light-converting adhesive film according to claim 1, characterized in that: The light-converting adhesive film comprises the following components in parts by weight: 100 parts of base resin, 0.05 parts of cross-linking agent, 1.0 parts of auxiliary cross-linking agent, 3.0 parts of coupling agent and 5.0 parts of grafted light conversion material.
3. The high-efficiency light-converting adhesive film according to claim 1 or 2, characterized in that: The particle size of the grafted light conversion material is 5.0 to 20.0 nm.
4. The high-efficiency light-converting adhesive film according to claim 1 or 2, characterized in that: The cross-linking agent is a peroxide cross-linking agent, which is selected from any one of dicumyl peroxide, di(tert-butylperoxyisopropyl)benzene or 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.
5. The high-efficiency light-converting adhesive film according to claim 1 or 2, characterized in that: The auxiliary crosslinking agent is selected from at least one of trimethylol triacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, N,N'-p-phenyl bismaleimide, zinc diacrylate and zinc dimethacrylate.
6. The method for preparing a high-efficiency light-converting adhesive film according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: S1. Preparation of grafted light conversion material: mixing the light conversion material or light conversion material precursor, the functional monomer containing vinyl, methoxy or amino functional groups, and the crosslinking initiator in a stirrer, and bonding the crosslinking initiator and the functional monomer to the light conversion material by microwave or infrared energy projection, thereby forming the grafted light conversion material; S2. Preparation of high-efficiency light-converting adhesive film: accurately weigh the base resin, cross-linking agent, auxiliary cross-linking agent, coupling agent and grafted light-converting material by weight, mix them thoroughly and add them into the extruder, cast them into a film through a die head, and heat treat them to obtain a high-efficiency light-converting adhesive film.